(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study was conducted at two primary health care centers in Al Hilla city which covered Al Gameyahprimary health care center and Al Kawthar primary health care center for the purpose of evaluating the useof growth chart and to determine mothers understanding toward the meaning of the weight chart in terms ofgrowth. All registered children aged 0-5 years who were living in areas served by the above two mentionedprimary health centers were included. The following results may be drawn on the objectives of the study.The proportion of registered children who possessed a chart was very high (99.8%). The proportion ofregistered children who acquired a chart at birth was high too (99.6%). It is of interest to find that the dateof birth of (99.6%) of children was registered and the weight at birth of (99.2%) of them was known too. Itwas found that only (90%) of study population had their weight charted on the curve of growth charts. Thestudy showed that no children of both sexes were attending regularly to have their weight charted in mostmonths of the year. The study generally depicted that the level of immunization of the children in study areawas remarkable and high.